CELLULAR GEOPOLYMERIC MATERIAL MADE BY ALUMINA-SILICATE WASTES-BASED NONCONVENTIONAL TECHNIQUE - Lucian Paunescu; Eniko Volceanov; Bogdan Valentin Paunescu (Nonconventional Technologies Review)
Geopolymer froth with excellent physio-mechanical, heat, and morphological features was made from a mix including fly ash and metallurgical slag as alumina-silicate industrial by-products. Using the metallurgical slag and montmorillonite as a nanomaterial constituted the composition novelty of starting mixture as well as the use as surfactant of a rarely applied material (sunflower oil) in making process of geopolymer froth were originality elements. Results were appreciable, the compression resistance reaching 6.7 at the final curing process and 4.9 MPa at early age and flexure resistance registering 3.3 MPa and 3.0 MPa at the final curing process and early age, respectively. The new cellular product is adequate for applications in construction as a lightweight insulating material, having better features by comparing with the traditional lightweight porous concrete.